Islamic Business Ethics: Case Study of Puspa Sharia Micro Business Actors in Bank Indonesia West Java Region in Bandung 2017 - Juliana Juliana; M. Adib Sulthan; Muhammad Fathir (Review of Islamic Economics and Finance (RIEF), 2019)
This research is based on problems in MSMEs, including poor administration, low product competitiveness, low human resources, lack of mastery of science, quality of service, and use of quality goods (Halal Thayyib). This study aimed to measure the level of implementation of Islamic Business Ethics for MSME players in the PUSPA Bank Indonesia program in West Java in Bandung in 2017. The research method used was descriptive quantitative with data analysis techniques using descriptive statistics. The number of research samples is 50 consumers from 4 MSMEs engaged in the service, food, and craft sectors. The results of the study show that the level of implementation of Islamic Business Ethics in micro-business actors guided by the PUSPA program in Bank Indonesia in West Java in 2017 is in outstanding criteria, dimensions that need to be improved are the orderly administrative dimensions and the dimensions of freedom with good criteria. At the same time, the dimensions of responsibility, justice, and truth are included in the criteria very well. The impact of this research shows the need for improvement of several indicators because it has implications for business progress and increased competitiveness of MSMEs themselves.